2020
DOI: 10.1155/2020/9182091
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomal SOCS2-AS1 Acts as a Novel Biomarker in Predicting the Diagnosis of Coronary Artery Disease

Abstract: Background and Aims. Critical roles of circulating exosomal long noncoding RNAs (lncRNAs) have been implicated in multiple diseases. However, little is known about their roles in coronary artery disease (CAD). The aim of the present study was to investigate the relationships between circulating exosomal lncRNAs and CAD and identify the aberrantly expressed disease-related lncRNAs as biomarkers in diagnosing CAD. Methods. The aberrantly expressed lncRNAs in plasma exosomes from CAD patients and controls were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Particularly, SOCS2-AS1 was significantly downregulated in HSCR patients. This lncRNA has been described in relation with prostate cancer and retinal Müller cell immune responses and has also been identified as a biomarker in coronary artery disease [67][68][69]. In this sense, SOCS2-AS1 would be a good candidate for further consideration as a gene related to the onset of HSCR and, therefore, of great interest to continue investigating in this line.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, SOCS2-AS1 was significantly downregulated in HSCR patients. This lncRNA has been described in relation with prostate cancer and retinal Müller cell immune responses and has also been identified as a biomarker in coronary artery disease [67][68][69]. In this sense, SOCS2-AS1 would be a good candidate for further consideration as a gene related to the onset of HSCR and, therefore, of great interest to continue investigating in this line.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been associated with various cardiovascular diseases in the literature, and studies have indicated that be used as a possible biomarker for the early diagnosis of the disease [30][31][32]. At the same time, lncRNAs may have a regulatory role in the pathogenesis of cardiovascular diseases [33].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have shown that exosomal lncRNAs may provide more stable and accurate lncRNA patterns according to disease subtypes. 9,19,30 Accordingly, enriched and specific lncRNAs in exosomes have gained increasing attention as noninvasive diagnostic biomarkers for cardiovascular diseases, including atherosclerosis (exosomal lncRNA HIF1A-AS1), 31 coronary artery disease (exosomal SOCS2-AS1), 32 and acute myocardial infarction (exosomal lncRNAs ENST00000556899.1 and ENS T00000575985.1). 33 However, the use of serum exosomal lncRNAs to predict and diagnose AF has not been sufficiently reported.…”
Section: Discussionmentioning
confidence: 99%